EFFECT OF AGRICULTURAL ECONNOMIC SURPLUS IN AGRICULTURAL GROWTH IN SELECTED ARAB CONNTRIES HAVE LIBERATION AND ECONCMIC CONTRROLLING POLICIES - Alaa M. Abdullah (Mesopotamia Journal of Agriculture)
This research interests in the topic of agricultural economic surplus as being described as one of the growth elements of agriculture especially in the developing countries and Arab countries .The follow control policies or economic liberation will give an important economic indicator about the development in such countries .Therefore ,the research aims at studying the direction that may have great agricultural surplus in order to cure the indicators of growing economics in these countries .Then ,we have the estimation of effects that may be created by changes of that surplus and the agricultural economic surplus in the range of agricultural growth for states that follow the policies of liberation and economic control which selected for time series (1980-2002) .Throughout the study ,we have reached to the result that the situations of agriculture in the Arab countries studied in the research whether they are countries of liberation policies or economic control reaches the type of self satisfying agricultures because of small farms and their dispersing here and there leading to lowering the estimated agricultural economic surplus .Also, the traditional agriculture leads to lowering of the capita share causing lowering in farmers savings with wide surplus i.e the work return is affected highly by most of it. This does not mean that the work is with high efficiency ,but the increase of work share at economic production levels reaching zero leading to the leak of the economic surplus away from agricultural growth efforts ,in addition, part of public consumption expenditure depends on the circumstances of the mentioned surplus.